2005
DOI: 10.1111/j.1442-2050.2005.00492.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of methylenetetrahydrofolate reductase and thymidylate synthase promoter polymorphisms with genetic susceptibility to esophageal and cardia cancer in a Chinese high-risk population

Abstract: Methylenetetrahydrofolate reductase (MTHFR) and thymidylate synthase (TS) are key enzymes in folate metabolism, which is essential for normal DNA methylation and synthesis. Common polymorphisms at the MTHFR nucleotides position 677 (C-T) and a 28-bp tandem repeat polymorphism (2R or 3R) in the TS promoter enhancer region (TSER) have been reported to be functional and are supposed to disturb the normal DNA methylation and synthesis leading to carcinogenesis. To investigate the association between these polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 28 publications
1
47
0
Order By: Relevance
“…In particular, these results suggest that the 677TT mutation in MTHFR reduces colon cancer risk, perhaps by increasing 5,10-methylenetetrahydrofolate levels for DNA synthesis, but that low folate intake or high alcohol consumption may negate some of the protective effect.It is generally believed that with sufficient folate intake, the risk of cancer in MTHFR 677CT or TT genotype carriers would be to reduced, since low activity of folate metabolic enzyme will not only help DNA synthesis reaction ,while adequate folate can but also provide sufficient methyl groups for DNA methylation process; oppositely, if the intake of folate is deficient, DNA synthesis, repair and the methylation process would all be affected. 5, 10-methylene THF supply deficiency would result in the difficulty of executing the protective function of MTHFR mutation genotype, so that the DNA methylation process would be disturbed (Wang et al, 2005;Yang et al, 2005). in this study, we found that the Dact1 gene methylation frequency in the TCC tissue from carriers of 1298 AC + AA and 677 TT + CT genotypes was significantly increased, which suggested that the effect of 1298AA polymorphism on DNA methylation is very likely due to the coexistence of the 677TT genotype (Friso et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, these results suggest that the 677TT mutation in MTHFR reduces colon cancer risk, perhaps by increasing 5,10-methylenetetrahydrofolate levels for DNA synthesis, but that low folate intake or high alcohol consumption may negate some of the protective effect.It is generally believed that with sufficient folate intake, the risk of cancer in MTHFR 677CT or TT genotype carriers would be to reduced, since low activity of folate metabolic enzyme will not only help DNA synthesis reaction ,while adequate folate can but also provide sufficient methyl groups for DNA methylation process; oppositely, if the intake of folate is deficient, DNA synthesis, repair and the methylation process would all be affected. 5, 10-methylene THF supply deficiency would result in the difficulty of executing the protective function of MTHFR mutation genotype, so that the DNA methylation process would be disturbed (Wang et al, 2005;Yang et al, 2005). in this study, we found that the Dact1 gene methylation frequency in the TCC tissue from carriers of 1298 AC + AA and 677 TT + CT genotypes was significantly increased, which suggested that the effect of 1298AA polymorphism on DNA methylation is very likely due to the coexistence of the 677TT genotype (Friso et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…TS plays an important role in folate metabolism. Using the methyltetrahydrofolic acid as a substrate, TS catalyses the methylation of deoxyuridylic acid, transferring it into deoxythymidylic acid, which is an important nucleotide in the synthesis and reparation of DNA [17] . This study showed that the expression of TS in ESCC was higher than that in normal tissue, and that the expression in moderately-and poorly-differentiated ESCC was higher than that in well-differentiated ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…In all studies, the cases were histologically confirmed (or historically based on pathology), and the controls were free of GC cancer (two studies, Sarbia et al 2005 andGraziano et al 2006, reported the use of healthy controls). Six studies stated that the controls were age-sex matched (Stolzenberg et al 2003;Kim et al 2005;Wang et al 2005;Shen et al 2005;Lacasana et al 2005;Graziano et al 2006). Studies were conducted in various populations of different ethnicities: five studies were conducted in populations of East Asian ethnicity (Miao et al 2002;Stolzenberg et al 2003;Kim et al 2005;Wang et al 2005;Shen et al 2005), two studies involved Caucasians (Sarbia et al 2005;Graziano et al 2005), and one study Mexicans (Lacasana et al 2005).…”
Section: Eligible Studiesmentioning
confidence: 99%
“…Six studies stated that the controls were age-sex matched (Stolzenberg et al 2003;Kim et al 2005;Wang et al 2005;Shen et al 2005;Lacasana et al 2005;Graziano et al 2006). Studies were conducted in various populations of different ethnicities: five studies were conducted in populations of East Asian ethnicity (Miao et al 2002;Stolzenberg et al 2003;Kim et al 2005;Wang et al 2005;Shen et al 2005), two studies involved Caucasians (Sarbia et al 2005;Graziano et al 2005), and one study Mexicans (Lacasana et al 2005). A list of all the details abstracted from these studies is provided in Tables 1 and 2.…”
Section: Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation